(untitled) (Global Journal of Medical Research, 2021)
Background: In women of reproductive age, thyroid illness is the second most frequent endocrine disorder. While overt thyroid disease is well known as a cause of infertility, the effects of mild thyroid dysfunction or thyroid autoimmunity are still unknown. Thyroid function may play a role in female reproduction, which is especially important when the cause of infertility is unknown. Objective: The study aims to determine the association of thyroid autoimmunity (antithyroglobulin and antithyroid peroxidase) and thyroid dysfunction (hypo-or hyperthyroidism) among women with infertility. Method: This retrospective case-control study was conducted from January 2020 to July 2021 at the Gynaecology Department of Patuakhali Medical College Hospital, Bangladesh. This study was purposefully selected for 220 cases, and cases were chosen by unique inclusion and exclusion criteria.